Time-restricted feeding can increase food-related impulsivity: a randomized controlled trial - AKTAÇ, ŞULE (My University, 2024)
Objectives: Although an increasing number of studies show that time-restricted feeding may improve metabolic health, studies examining the behavioral effects of this eating pattern are limited. This study examined the effect of time-restricted feeding on impulsivity in adults. Methods: Thirty adults aged 25–41 years participated in this randomized controlled trial. The intervention group followed time-restricted feeding for 4 weeks and there was no energy restriction in the intervention group (n = 15) or control group (n = 15). Impulsivity was assessed before and after the intervention with the Barratt Impulsiveness Scale and the Go/NoGo task. Results: The compliance rate (the percentage of days when participants had a feeding time of ≤ 8 hours/day) of the intervention group to the time-restricted feeding pattern was 92.38 ± 4.24%. The Barratt Impulsiveness Scale-11 total score of the intervention group increased from 55.53 ± 6.37 to 59.47 ± 7.67 (p = 0.02). During the Go/NoGo task, an indicator of inhibitory control, the reaction time to food and non-food stimuli was significantly shortened in the intervention group (respectively; p = 0.009, p = 0.01). In the control group, no significant change was detected in impulsivity determined by the BIS-11 or Go/NoGo task. Discussion: This study showed that although time-restricted feeding may reduce body weight, it can lead to increased impulsivity and impaired inhibitory control. Trial registration:ClinicalTrials.gov identifier: NCT04960969.
Keywords: Tıp; Beslenme ve Dietetik; Tarımsal Bilimler; Ziraat; Yaşam Bilimleri; Sağlık Bilimleri; Temel Tıp Bilimleri; Temel Bilimler; Medicine; Nutrition and Dietetics; Agricultural Sciences; Agriculture; Life Sciences; Health Sciences; Fundamental Medical Sciences; Natural Sciences; Tarım ve Çevre Bilimleri (AGE); Klinik Tıp (MED); Yaşam Bilimleri (LIFE); Tarım Bilimleri; Klinik Tıp; Sinirbilim ve Davranış; BESLENME VE DİYETETİK; TIP, GENEL & DAHİLİ; SİNİR BİLİMİ; Agriculture & Environment Sciences (AGE); Clinical Medicine (MED); Life Sciences (LIFE); AGRICULTURAL SCIENCES; CLINICAL MEDICINE; NEUROSCIENCE & BEHAVIOR; NUTRITION & DIETETICS; MEDICINE, GENERAL & INTERNAL; NEUROSCIENCES; Tıp (çeşitli); Genel Sinirbilim; Beslenme ve Diyetetik; Medicine (miscellaneous); General Neuroscience; diet; fasting; feeding and eating disorders; feeding behavior; Impulsive behavior; ‌neurosciences; ‌nutrition therapy; ‌nutritional sciences